2018
DOI: 10.1002/nop2.165
|View full text |Cite
|
Sign up to set email alerts
|

The impact of implementing a fall prevention educational session for community‐dwelling physical therapy patients

Abstract: AimThe aim of this study was to evaluate the impact of a fall prevention educational session on fall risk knowledge, use of fall prevention interventions and the number of falls in community‐dwelling older persons attending physical therapy.DesignThis pilot study used a mixed method design consisting of a quantitative pretest–posttest quasi‐experimental design followed by a qualitative interview.MethodAn educational intervention was given with pre‐ and posttest questionnaires to determine the outcome measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 28 publications
2
30
1
2
Order By: Relevance
“…Another explanation is that, after the intervention, some participants may have started to pay attention to their vision and hearing needs since recommendations about the correct use of eyeglasses were provided and resulted in a significant change in the vision compensation behavior of the IG. This was also found in a previous study (Ott, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Another explanation is that, after the intervention, some participants may have started to pay attention to their vision and hearing needs since recommendations about the correct use of eyeglasses were provided and resulted in a significant change in the vision compensation behavior of the IG. This was also found in a previous study (Ott, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…These results are similar to those reported in a randomized trial which reported, after 12‐ and 52‐weeks postintervention, a significant change in fall prevention behaviors (Kamei et al., 2015), and to those reported in a quasi‐experimental research, in which the researchers provided instructions to improve the safety of older adults’ homes and resulted in important changes in the home environment of the participants (Ott, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…On the contrary, all studies did not report any association between fall risk awareness or knowledge and fall preventive behaviour. Despite that, theoretical principles supported the relationship of knowledge to behaviour change as demonstrated in numerous studies (Miller, 2010;Ott, 2018;Punlomso et al, 2020). Using an interactive and familiar activity to conduct FPE may increase the likelihood of older individuals' behaviour participation in the prevention process and learning (Flint et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there was no further explanation in a study by Chen (2013). Khong et al, 2017;Ott, 2018). Two studies focused on home or environmental risks (Kamei et al, 2015;Schepens et al, 2011), and another study provided education on environmental risks and exercise information (Chen, 2013).…”
Section: Fpe and Behaviour Change-related Outcomementioning
confidence: 99%
“…The HBM consists of health person's beliefs (risk susceptibility, risk severity, benefits to action, and barriers to action), self-efficacy, and cues to action 12 . Nowadays, it has been widely used in health promotion and behavioral modification programs in older persons [13][14][15] . The purposes of this present study were to examine effects of HBM-OEP on postural balance and quadriceps muscle strength and to investigate levels of knowledge, perception, and behavior related to fall prevention in communitydwelling older persons.…”
Section: Introductionmentioning
confidence: 99%